Oesofagogastroduodenal endoscopic features in patientswith cirrhotic partal hypertension - M. Enver DOLAR,; Mahmut ÖZTÜRK,; Macit GÜLTEN,; S. Giray NAK,; Faruk MEMİK, (Turkish Journal of Gastroenterology, 2020)
-